Possible Causes on Students’ Anxiety in Speaking English at Junior High School - Maisaroh Maisaroh (UICELL, 2022)
Anxiety is a situation where a person is filled with feelings of tension, worry, and fear of something that will be faced. Everyone has experienced anxiety, including students. Usually, students' feelings of worry arise during the learning process. Anxiety in the learning process can be a serious obstacle when studying certain subjects. the researcher found a phenomenon that a student in the ninth grade of junior high school. The purpose of this study was to find out the problems that cause students' anxiety in discussing English and to find out the effect of students' anxiety in discussing English in nine grade of junior high school. In this study, researchers used descriptive research that concentrated on the description. In collecting the data researcher used two procedures. These are observation and interview. The creative findings from this research are some students that feel anxious because of the methods used by the teacher in learning, the learning is quite difficult and the teacher's status as the child of the head of the foundation influences students' concerns. And because the teacher is the son is the head of school foundation (nyai) and of course because doesn’t have many vocabularies. The influence is both positive and negative. Negative is a state of anxiety, worry, and or fear that makes a person unable to perform certain tasks or functions in a situation, even traumatizing students. And positive students make more communicative and motivated students for learn. Key words: Anxiety, Speaking English